2001
DOI: 10.1002/dmrr.214
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of diabetes mellitus and liver cancer in Japan

Abstract: A significant association between diabetes and liver cancer was observed. Moreover, this association was modified by hepatitis and cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 34 publications
7
58
5
Order By: Relevance
“…The association between DM and HCC was found to be modified by hepatitis virus infection, heavy alcohol consumption, and other known risk factors. 51,[61][62][63] Fujino et al 2001 61 found that the relative risk (RR) of DM for primary liver cancers was 2.06 (95% CI, 1.01-4.19) after adjustment for smoking, alcohol, and diseases associated with liver cancer in a prospective study of diabetes and liver cancers in Japan. Diabetes increased the risk of liver cancers in patients with hepatitis and/or cirrhosis and it was concluded and confirmed by a few subsequent reported studies, although the modified factors were different in different studies.…”
Section: Impact Of Diabetes As Risk Factor In Hepatocellular Carcinomamentioning
confidence: 99%
“…The association between DM and HCC was found to be modified by hepatitis virus infection, heavy alcohol consumption, and other known risk factors. 51,[61][62][63] Fujino et al 2001 61 found that the relative risk (RR) of DM for primary liver cancers was 2.06 (95% CI, 1.01-4.19) after adjustment for smoking, alcohol, and diseases associated with liver cancer in a prospective study of diabetes and liver cancers in Japan. Diabetes increased the risk of liver cancers in patients with hepatitis and/or cirrhosis and it was concluded and confirmed by a few subsequent reported studies, although the modified factors were different in different studies.…”
Section: Impact Of Diabetes As Risk Factor In Hepatocellular Carcinomamentioning
confidence: 99%
“…13 The followup has been described in detail elsewhere. 14,15 Briefly, the baseline survey was conducted from 1986 to 1989. We invited all inhabitants aged from 30 to 79 years living in A town, B village, and selected districts of C city and D town (15,417 subjects in total) to participate in a self-administrated questionnaire survey.…”
Section: Study Populationmentioning
confidence: 99%
“…Our cohort study was started in Fukuoka Prefecture in 1986 -89, and the follow-up method has been described elsewhere (Fujino et al, 2001;Mizoue et al, 2000;Utoguchi et al, 1997). The number of subjects who were invited to participate and fill in a self-administered questionnaire was 15 417.…”
Section: Study Populationmentioning
confidence: 99%